Analysis of critical knowledge in a coffee supply chain - Dong Lianghui (2019)
© 2019 IEEE. Good quality coffee has high economic value in the global market. However, the quality of coffee is vulnerable to natural factors and operation factors. Because the coffee supply chain is a complex operation process, which involves cultivating, harvesting, processing, roasting, and consumption. Stakeholders should be responsible for the quality of products in each process. In other words, if stakeholders lack critical knowledge in the coffee supply chain, improper operations of stakeholders will damage the quality of coffee. This paper aims to analyze the critical knowledge existed in the coffee supply chain. The research starts with an overview of the related stakeholders, products, processes, and activities in the coffee supply chain. Expert interviews are used to acquire knowledge and knowledge maps are used as tools. The final part of this paper is presented the critical knowledge in terms of the knowledge map. The results show that the most critical knowledge is focused on the upstream processes from original farmers and community enterprises which is directly affected to the taste of coffee in quality.